Exercise Prescription Patterns in Patients Treated with Vestibular Rehabilitation After Concussion. (12th July 2012) - Alsalaheen, Bara A.; Whitney, Susan L.; Mucha, Anne; Morris, Laura O.; Furman, Joseph M.; Sparto, Patrick J.
Abstract Background and Purpose Individuals with concussion often complain of persistent dizziness and imbalance, and these problems have been treated with vestibular rehabilitation exercises. The purpose of this study is to describe the vestibular rehabilitation exercise prescriptions provided to individuals after concussion. Methods A retrospective chart review of vestibular rehabilitation home exercise programmes prescribed by physical therapists for 104 participants who were diagnosed with concussion was conducted. Each of the exercises was classified by exercise type, duration and frequency. Frequency counts of the most common exercise types were recorded. Exercise progression patterns were examined by determining how exercise types were modified from visit to visit. Results Eye–head coordination exercises were the most commonly prescribed exercise type (in 95% of participants), followed by standing static balance exercises (in 88% of participants), and ambulation exercises (in 76% of participants). Conclusions Understanding the prescription patterns of expert clinicians may elucidate the vestibular‐related impairments of individuals after concussion and may provide a resource for therapists who may be starting vestibular rehabilitation programmes for management of individuals with concussion. To improve quality of care, future research should be directed to relate outcomes to the exercise prescription patterns. Copyright © 2012 John Wiley & Sons, Ltd.